A Translation Analysis Of English Modal Verbs In The First Phone Call From Heaven Novel Into Telepon Pertama Dari Surga By Julanda Tantani - Duereh, Miss. Robeeah, Dr. Dwi Haryanti, M.Hum, Mauly Halwat Hikmat, Ph. D (2015)
The research paper analysis English modal verb in The First Phone Call from Heaven and its translation. The study aims (1) to clarify the translation variations of English modal verb in the novel The First Phone Call from Heaven and its translation and (2) to describe the accuracy of the translation in the novel. The type of this research is descriptive qualitative research. The object of the study is the novel entitled The First Phone Call from Heaven and its translation. The data of this study is English modal verb found in The First Phone Call from Heaven novel. Data source used in this research are the documentation of the data research paper and the informants. The researcher uses document, and questionnaire, in collecting data. The data are analyzed by using comparing method. Based on the analysis, there are 4 types of English modal verb. They are English modal verb translated into Indonesian modal verb consist of 280 data or 63,6%, 8 data or 1,8% English modal verb translated into adverb, 28 data or 4,1% English modal verb translated into adjective and 124 data or 28,1% deleted or omitted. From 440 English modal verbs there are 93 data or 21,1 % accurate, 344 data or 78,2% less accurate and 3 data or 0,7% not accurate. It can be concluded that the English modal verb translation variations are less accurate.